Feeding Rumensin to yearling heifers on late-summer grass - M. Jensen; R. Held; E.F. Smith; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1982)
Rumensin was self-fed in a loose salt mixture to yearling heifers on late-summer bluestem pasture (August to November). They ate 0.036 lbs. of salt mixture (124 mg of Rumensin) daily, but performance did not improve.
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Rumensin; Heifers; Bluestem pasture